1999
DOI: 10.1042/bj3420269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoreleased cADP-ribose on calcium transients and calcium sparks in myocytes isolated from guinea-pig and rat ventricle

Abstract: Actions of photoreleased cADP-ribose (cADPR), a novel regulator of calcium-induced calcium release (CICR) from ryanodine-sensitive stores, were investigated in cardiac myocytes. Photoreleased cADPR caused an increase in the magnitude of whole-cell calcium transients studied in mammalian cardiac ventricular myocytes (both guinea-pig and rat) using confocal microscopy). Approx. 15 s was required following photorelease of cADPR for the development of its maximal effect. Photoreleased cADPR also increased the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…At a higher concentration (500 µM), cADPR also failed to affect the rate of Ca 2+ removal when photolysed up to 10 seconds before depolarization but significantly increased the rate when photolysed 15 seconds beforehand (P<0.05; Table 2), a time consistent with the delays inherent in cADPR effects (e.g. Cui et al, 1999); the reason for the delay is not understood.…”
Section: Effect Of Cadpr On [Ca 2+ ]C Declinementioning
confidence: 54%
See 1 more Smart Citation
“…At a higher concentration (500 µM), cADPR also failed to affect the rate of Ca 2+ removal when photolysed up to 10 seconds before depolarization but significantly increased the rate when photolysed 15 seconds beforehand (P<0.05; Table 2), a time consistent with the delays inherent in cADPR effects (e.g. Cui et al, 1999); the reason for the delay is not understood.…”
Section: Effect Of Cadpr On [Ca 2+ ]C Declinementioning
confidence: 54%
“…This delay was attributed to the time required for the SR Ca 2+ content to be increased following SERCA activation by cADPR (Lukyanenko et al, 2001). This proposal could explain the frequently observed pronounced delay in the onset of cADPR activity (Cui et al, 1999;Aarhus et al, 1995;Li et al, 2000).…”
mentioning
confidence: 76%
“…This proposal has not been effectively countered by studies on ventricular myocytes, which exclusively express RyR2. This is due to the fact that the principal regulatory effect of cADPR with respect to RyR2 is to increase the sensitivity of this RyR subtype to Ca 2ϩ -induced Ca 2ϩ release (8,9), and in light of the fact that the sensitivity of RyRs to Ca 2ϩ -induced Ca 2ϩ release may be augmented by an increase in Ca 2ϩ concentration within the cytoplasm and/or S/ER lumen (15).…”
Section: Intracellular Camentioning
confidence: 99%
“…Although a wealth of evidence across a variety of cell types (3)(4)(5)(6)(7)(8)(9) supports the original proposal that cADPR activates RyRs (10), studies on reconstituted RyRs in lipid bilayers have failed to conclusively demonstrate direct regulation of these channels by cADPR (11), and it has been suggested that cADPR may initiate Ca 2ϩ signals via RyRs and IP 3 Rs by promoting Ca 2ϩ uptake into the S/ER by S/ER Ca 2ϩ ATPases (SERCA) (12)(13)(14). This proposal has not been effectively countered by studies on ventricular myocytes, which exclusively express RyR2.…”
Section: Intracellular Camentioning
confidence: 99%
“…In contrast, a study carried out in rat ventricular myocytes using caged cADPR suggests that cADPR does not regulate sarcoplasmic reticulum Ca 2ϩ release (25). However, work from several groups strongly suggests the following possibilities for cardiac myocytes: (i) that the enzymatic machinery for synthesis of cADPR is expressed (26,27); (ii) that cADPR increases both the amplitude of whole cell Ca 2ϩ transients and the frequency of Ca 2ϩ sparks in rat and guinea pig isolated myocytes (28); and (iii) that Ca 2ϩ signaling and contractions in electrically driven guinea pig or rat cardiac myocytes are sensitive to the specific cADPR antagonists 8-NH 2 -cADPR and 8-Br-cADPR (29,30).…”
Section: Discussionmentioning
confidence: 79%